Analisis Aliran Rantai Pasok Produk Koffie Hiedeung CV Toean Koffie di Kabupaten Karawang - Anggaresti, Elsa; Abubakar, Abubakar; Mahatmayana, I Ketut Manu (Paspalum: Jurnal Ilmiah Pertanian, 2024)
Increasing coffee consumption in Indonesia provides opportunities for the coffee processing industry. CV Toean Koffie is one of the companies in Karawang Regency engaged in coffee processing, which is involved in providing added value and brand branding, the product is known as Koffie Hideung. The supply of coffee beans for Koffie Hideung production is supplied by the farmer communities on the Sanggabuana Mountains in Karawang. The supply chain flow of Koffie Hideung products starts from the farmer level as a supplier to product marketing to consumers. The supply chain concept basically has interconnected aspects including the flow of goods, financial flow, and information flow which will determine the continuity of the supply chain performance mechanism properly. Good supply chain performance is determined by the role of the supply chain members involved. This study aims to analyze the supply chain conditions of Koffie Hideung products using the Food Supply Chain Network (FSCN) model. Based on the results of the analysis, the Food Supply Chain Network (FSCN) model includes 6 aspects consisting of, supply chain structure, supply chain objectives, resources involved, business processes in the supply chain, supply chain management, and supply chain performance. The supply chain structure of Koffie Hideung products involves a certain process from the production of coffee beans in farmers, the manufacturing process by CV Toean Koffie, distribution, to the final consumption by customers.